2022
DOI: 10.1111/mec.16719
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in floral availability leads to periods of resource limitation and affects diet specificity in a generalist pollinator

Abstract: N. (2022). Temporal change in floral availability leads to periods of resource limitation and affects diet specificity in a generalist pollinator. Molecular Ecology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…Finally, our third Special Issue, Insights into Ecological & Evolutionary Processes via Community Metabarcoding includes ‘papers that highlight the power of high‐throughput sequencing (HTS) data to address classic questions in ecology and evolution, particularly focused on metabarcoding (amplicon) datasets in conjunction with complementary ‐omics data types and/or models/theory to infer overall ecosystem processes’ (Gillespie et al., 2023). The impressive collection of 44 manuscripts covers a wide range of topics: community assembly processes (Andujar et al., 2022; Arjona et al., 2022; Emerson et al., 2022; Govender et al., 2022; Guerrieri et al., 2022; Ip, Chang, Oh, et al., 2022; Kiemel et al., 2022; Li et al., 2022; Macheriotou et al., 2023; Menéndez‐Serra et al., 2023; Nappi et al., 2022; Noguerales et al., 2023; Overcast et al., 2023; Pino et al., 2023; Van der Loos et al., 2022; Wang et al., 2022), interaction networks (Ando et al., 2022; Bell et al., 2022; Dürrbaum et al., 2022; Encinas‐Viso et al., 2022; Ficetola & Taberlet, 2023; Graham et al., 2022; Ip, Chang, Tun, et al., 2022; Lowe et al., 2022; Lu et al., 2022; Lue et al., 2022; Pitteloud et al., 2022; Srivathsan et al., 2022; Tommasi et al., 2022), cross‐scale interactions and microbiomes (Brinker et al., 2022; Câmara dos Reis et al., 2022; Hu et al., 2022; Kivistik et al., 2022; Manthey et al., 2022; Merges et al., 2022; Michel et al., 2022; Molina et al., 2022; Navine et al., 2022; Pereira et al., 2022; Perez‐Lamarque & Morlon, 2022; Rolshausen et al., 2022), and invasive species/homogenization (Andrés et al., 2023; Graham et al., 2022; Hampel et al., 2022; Kennedy et al., 2022; Overcast et al., …”
Section: Highlights Of 2023mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our third Special Issue, Insights into Ecological & Evolutionary Processes via Community Metabarcoding includes ‘papers that highlight the power of high‐throughput sequencing (HTS) data to address classic questions in ecology and evolution, particularly focused on metabarcoding (amplicon) datasets in conjunction with complementary ‐omics data types and/or models/theory to infer overall ecosystem processes’ (Gillespie et al., 2023). The impressive collection of 44 manuscripts covers a wide range of topics: community assembly processes (Andujar et al., 2022; Arjona et al., 2022; Emerson et al., 2022; Govender et al., 2022; Guerrieri et al., 2022; Ip, Chang, Oh, et al., 2022; Kiemel et al., 2022; Li et al., 2022; Macheriotou et al., 2023; Menéndez‐Serra et al., 2023; Nappi et al., 2022; Noguerales et al., 2023; Overcast et al., 2023; Pino et al., 2023; Van der Loos et al., 2022; Wang et al., 2022), interaction networks (Ando et al., 2022; Bell et al., 2022; Dürrbaum et al., 2022; Encinas‐Viso et al., 2022; Ficetola & Taberlet, 2023; Graham et al., 2022; Ip, Chang, Tun, et al., 2022; Lowe et al., 2022; Lu et al., 2022; Lue et al., 2022; Pitteloud et al., 2022; Srivathsan et al., 2022; Tommasi et al., 2022), cross‐scale interactions and microbiomes (Brinker et al., 2022; Câmara dos Reis et al., 2022; Hu et al., 2022; Kivistik et al., 2022; Manthey et al., 2022; Merges et al., 2022; Michel et al., 2022; Molina et al., 2022; Navine et al., 2022; Pereira et al., 2022; Perez‐Lamarque & Morlon, 2022; Rolshausen et al., 2022), and invasive species/homogenization (Andrés et al., 2023; Graham et al., 2022; Hampel et al., 2022; Kennedy et al., 2022; Overcast et al., …”
Section: Highlights Of 2023mentioning
confidence: 99%
“…Collectively the articles in this Special Issue 'underline the huge impact of the anthropogenic environment in microbial evolution, including the emergence and spread of pathogens as well as the benefits provided by domesticated or mutualistic fungi and bacteria'(Giraud et al, 2023).Finally, our third Special Issue, Insights into Ecological & Evolutionary Processes via Community Metabarcoding includes 'papers that highlight the power of high-throughput sequencing (HTS) data to address classic questions in ecology and evolution, particularly focused on metabarcoding (amplicon) datasets in conjunction with complementary -omics data types and/or models/theory to infer overall ecosystem processes'(Gillespie et al, 2023). The impressive collection of 44 manuscripts covers a wide range of topics: community assembly processes(Andujar et al, 2022;Arjona et al, 2022;Emerson et al, 2022;Govender et al, 2022;Guerrieri et al, 2022;Ip, Chang, Oh, et al, 2022;Kiemel et al, 2022;Li et al, 2022;Macheriotou et al, 2023;Menéndez-Serra et al, 2023;Nappi et al, 2022;Noguerales et al, 2023;Overcast et al, 2023;Pino et al, 2023;Van der Loos et al, 2022;Wang et al, 2022), interaction networks(Ando et al, 2022;Bell et al, 2022;Dürrbaum et al, 2022;Encinas-Viso et al, 2022;Ficetola & Taberlet, 2023;Graham et al, 2022;Ip, Chang, Tun, et al, 2022;Lowe et al, 2022;Lu et al, 2022;Lue et al, 2022;Pitteloud et al, 2022;Srivathsan et al, 2022;Tommasi et al, 2022), cross-scale interactions and microbiomes(Brinker et al, 2022;Câmara dos Reis et al, 2022...…”
mentioning
confidence: 99%
“…Foraging animals frequently face the challenge of the resource environment changing over time and space. Changes include phenological fluctuations in the availability and quality of alternative resources (Cotton, 2007; Lowe et al, 2022; Stephens et al, 2019) and resource depletion by competitors (Balfour et al, 2015; Damas-Moreira et al, 2020; Page & Williams, 2023; Valls-Fox et al, 2018). In such circumstances, foragers may switch from one resource type to another (Lowe et al, 2022; Mitchell, 1990; Page & Williams, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Lowe et al. (2022) provides an empirical example in which they used pollen DNA metabarcoding of honey samples in the honeybee ( Apis mellifera ) to reveal seasonal changes in diet specialisation according to resource availability. Because the degree of specialisation is linked to network resilience, the study highlighted seasonal changes in network vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…They consider how the approach can be applied to understanding key questions in global change ecology, in particular, how interactions change through space and time, including the impacts of climate and other anthropogenic stressors.Similar studies have shown how environmental DNA (eDNA) from flowers can be used to identify the community of pollinating bumblebees and has the potential to reveal complex networks(Harper et al, 2023). The paper byLowe et al (2022) provides an empirical example in which they used pollen DNA metabarcoding of honey samples in the honeybee (Apis mellifera) to reveal seasonal changes in diet specialisation according to resource availability.Because the degree of specialisation is linked to network resilience, the study highlighted seasonal changes in network vulnerability.Along similar lines, the paper by Encinas-Viso et al (2022) focuses on factors that might drive beta diversity in alpine plant-pollinator communities. By analysing insect pollen loads they showed that metabarcoding data generated networks that were more diverse but much less specialised compared to observational data.…”
mentioning
confidence: 99%